The Treatment of Financial Reporting with Artificial Neural Networks - Mayta H., Rosmeri (2001)
In this paper the most recent and remarkable innovations in paradigms arise; expert systems and artificial neural networks, describing both systems first and then reviewing the work areas. Finally, because of its novelty, highlights the most relevqantes applications of neural models using financial information; the case of business failure analysis and prediction in losmercados financierosm doned complementarity between statistical and neural models are playing an effective role.